IMPLEMENTASI PRINSIP-PRINISP HUKUM KONTRAK INTERNASIONAL ANTARA PERUSAHAAN GLOBEX DARI AMERIKA DENGAN PEMERINTAHAN RUMANIA - Kartika Cahyaningtyas (JURNAL SUMBER HUKUM, 2024)
This study examines and analyzes the agreement made by an American company called Globex with the Romanian Government, there are still things that are not appropriate in making the agreement. This is related to the choice of law or choice of law is not explicitly stated, so that the parties make their own justification so as not to be considered to have broken their promises or default. Another reason that has not been implemented perfectly is related to the principles of International Contract Law in making international agreements. The method used in normative research with a problem approach is the case approach. The case that occurred between an American company called Globex and the Romanian Government had to make an international agreement in detail and firmly regarding rights and obligations as well as risks including the consequences, which before making an agreement must pay attention to the provisions that apply. This is important because it is related if there is a party who breaks their promise or defaults.